Displacement of lower third molar into the lateral pharyngeal space in a case of mandibular angle fracture: An unusual complication - Akash Kasatwar; Nitin Bhola; Rajiv Borle; K Rajanikanth (Wolters Kluwer Medknow Publications, 2016)
Fracture of the angle of the mandible accounts for nearly one-third of all fractures involved. The presence of lower third molar increases the risk of fracture in angle region. The third molar acts as an area of weakness leading to fracture lines passing medially, distally, and occasionally through it. Angle fracture leads to the mobility of the third molar and sometimes its displacement. Third molars maintain its position in favorable fracture and can be displaced in unfavorable fractures. Displacement of lower third molar in lateral pharyngeal space due to mandibular fracture is not seen commonly. To our knowledge, this is the first reported incidence of displacement of the third molar into lateral pharyngeal space in a case of mandibular fracture.